Acute and Subacute Toxicity Profile of Asparagus racemosus root extract, Isoprinosine and Shatvari Syrup in Swiss Albino Mice - B. Satheesh Kumar Bhandary, K. P. Sharmila, N. Suchetha Kumari, Vadisha S. Bhat, Ronald Fernandes (Journal of Applied Pharmaceutical Science, 2017)
The present study was carried out to evaluate the safety of Asparagus racemosus root ethanol extract, isoprinosine and shatvari syrup by acute ad subacute toxicity studies. Acute and subacute oral toxicity study was conducted according to the guidelines of OECD 425 and 407 respectively. In acute oral toxicity, mice were administered with 2000 mg/ kg body weight of ARE, STR and IPR respectively and were observed continuously for the first 4 h and for the next 24 h and for the following 48 h after administration of the test substances. In the subacute toxicity studies, ARE, STR and IPR were given orally at the dose of 2000 mg/ kg body weight daily for 28 consecutive days. General behavior, adverse effects and mortality were observed throughout the experimental period. Food and water intake, body and organ weight variations, hematological and biochemical parameters, histopathological changes were assessed. No mortality or signs of acute toxicity was observed in the mice at the maximum tolerable dose of 2000 mg/kg body weight. The results did not show any treatment related abnormalities in terms of hematological and biochemical parameters in sub-acute toxicity tests. No significant differences in body weight and organ weight between the control and treated groups were observed. Histopathological analysis showed no morphological changes of the vital organs namely liver and kidney between the control and treated groups. These results concluded that ARE, STR and IPR did not cause any mortality and signs of toxicity at maximum tolerable dose of 2000 mg/kg body weight in mice.
Keywords: Acute, subacute, Asparagus racemosus, Isoprinosine, Shatvari.